2018
DOI: 10.1093/aob/mcy024
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting plant height can improve the control of rain-borne diseases in wheat cultivar mixture: modelling splash dispersal in 3-D canopies

Abstract: These results suggest that mixture effects on spore dispersal could be modulated by an adequate choice of architectural characteristics of cultivars. In particular, even small differences in plant height could reduce spore dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
0
27
1
1
Order By: Relevance
“…(2013) found that a susceptible cultivar was consistently protected in a mixture under low to moderate STB levels. Subsequent greenhouse experimentation (Vidal et al ., 2017) and a modelling study (Vidal et al ., 2018) have demonstrated the importance of canopy structure for the efficacy of a mixture.…”
Section: Introductionmentioning
confidence: 99%
“…(2013) found that a susceptible cultivar was consistently protected in a mixture under low to moderate STB levels. Subsequent greenhouse experimentation (Vidal et al ., 2017) and a modelling study (Vidal et al ., 2018) have demonstrated the importance of canopy structure for the efficacy of a mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pathogen dispersal mode may influence relationships with plant traits. For example, taller plants may be more susceptible to wind dispersed pathogens, whereas plants with foliage low to the ground may be more affected by pathogens from the soil surface (Marquis et al 2001;Robert et al 2018;Vidal et al 2018), suggesting that traits conferring tolerance, resistance, and escape may be pathogen dependent.…”
Section: Context Dependencementioning
confidence: 99%
“…These traits could be used to assist plant breeders in the selection of soybean genotypes. For example, they are used as indicators to identify early maturing soybean cultivars that can reduce yield losses due to diseases [59,60] and insect-pest complexes [61]. From a technical perspective, geometric traits can also be accurately measured using other imaging sensors, such as light detection and ranging (LIDAR) sensors, and color indices can be accurately acquired using a near-infrared spectroscopy camera.…”
Section: Future Workmentioning
confidence: 99%